Electric field-induced changes in the ferroelastic behavior of (Na1/2Bi1/2)TiO3-BaTiO3. Issue 14 (November 2018) - Martin, Alexander; Khansur, Neamul H.; Webber, Kyle G.
Abstract: In this study, the macroscopic mechanical behavior was characterized for poled and unpoled polycrystalline (1− x )(Na1/2 Bi1/2 )TiO3 - x BaTiO3 (NBT- x BT) for compositions across the morphotropic phase boundary (MPB). Due to a field-induced ferroelectric phase transformation, NBT- x BT compositions near the MPB ( x = 6–7 mol%) showed a significant decrease in the coercive stress for electrically poled samples. The apparent difference in mechanical behavior is suggested to be due to an irreversible electric-field-induced transformation to long-range ferroelectric order in the poled samples. The results indicate a significant difference in the critical stresses for the relaxor-ferroelectric transition and ferroelastic domain wall motion, which can have important effects on applications for lead-free ferroelectrics. To further illustrate this, a method was developed to electrically depole NBT- x BT at room temperature, resulting in an unpoled NBT- x BT material with long-range ferroelectric order. Mechanical testing revealed analogous macroscopic ferroelastic behavior to the poled samples, despite the lack of a piezoelectric response.